A serologic survey of Mycoplasma spp. in farmed bison (Bison bison) herds in western Canada. (July 2017) - Bras, Ana L.; Suleman, Muhammad; Woodbury, Murray; Register, Karen; Barkema, Herman W.; Perez-Casal, Jose; Windeyer, M. Claire
Mycoplasma bovis is emerging as an important pathogen of farmed bison in North America and is associated with high morbidity and mortality in affected herds. We developed an in-house ELISA to detect antibodies against Mycoplasma spp. in bison sera. The aims of the study were to estimate the seroprevalence against Mycoplasma spp. in bison herds with or without past history of M. bovis –associated disease, and to determine potential risk factors for seropositivity to Mycoplasma spp. in farmed bison in western Canada. A total of 858 serum samples were collected from bison >1 y of age from 19 bison herds. The individual and herd-level seroprevalence of Mycoplasma spp. was 12% and 79%, respectively. The proportion of seropositive animals was 0–41% and 0–9% for herds with or without a history of M. bovis –associated disease, respectively. Mycoplasma spp. appear to be widespread in bison in Manitoba, Saskatchewan, and Alberta. Eight of 11 herds with no history of M. bovis –associated disease were seropositive for Mycoplasma spp., which suggests that bison can be subclinically infected with Mycoplasma spp., or that infection may be underdiagnosed. Although not specific to M. bovis, the in-house ELISA developed to detect antibodies against Mycoplasma spp. may prove to be a valuable herd-level screening tool, providing insight needed for the development of appropriate prevention and control measures for Mycoplasma -related disease in bison herds.